Pengaruh Kualitas Produk, Brand Awareness dan Celebrity Endorser Terhadap Keputusan Pembelian pada Produk Hand and Body Lotion Nivea - Sheilaika Nur Wahyuningsih; Isa, Muzakar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the impact of product quality, brand awareness, and celebrity endorsers on purchasing decisions for Nivea hand and body lotion. This research employs an explanatory research method with a quantitative approach, involving 200 female respondents aged 10–26 years residing in Surakarta City. Data collection was conducted through an online questionnaire using a 5-point Likert scale. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings indicate that product quality, brand awareness, and the use of celebrity endorsers have a positive and significant influence on purchasing decisions. The study also identifies limitations, including the relatively small sample size and potential response bias. Therefore, it is recommended that the company enhance product quality, maintain positive perceptions through social media, and carefully select appropriate celebrity endorsers. Future research is encouraged to involve a larger number of respondents to improve the representativeness of the results.